Comparison of Propofol-Fentanyl with Midazolam-Ketamine Combination in Pediatric Patients Undergoing Kidney Biopsy (Iranian Journal of Kidney Diseases, 2022)
Introduction. Kidney biopsy is a procedure of choice for the diagnosis of many kidney diseases. In children it is performed with the use of sedatives. The aim of this study was to compare the combination of propofol/fentanyl with midazolam/ketamine for sedation in pediatric patients undergoing kidney biopsy. Methods. In this double-blinded clinical trial, seventeen children, candidate of kidney biopsy were included and randomized into two groups. One group received Midazolam/Ketamine with doses of 30 to 50 μg/kg and 0.25 to 1 mg/kg, and the other group were sedated with propofol/fentanyl combination in doses of 0.5 to 1 mg/kg and 0.5 to 1 mg/kg, respectively. Administration time, medication doses, total procedure time, need for analgesic use after the procedure, and patient relaxation, with no agitation during and after the biopsy were recorded. Results. Nine patients received midazolam/ketamine and eight received propofol/fentanyl. None of them experienced vomiting or itching after sedation. There were no meaningful differences in qualitative variables of the need for pain relief between two groups. Regarding the distribution of pain at the time of sedation, and 1, 3, 6, and 24 hours after sedation, there was no significant statistical difference between the two groups. There was also no significant statistical difference between the two groups, regarding patients’ relaxation during, and 1, 3, 6, and 24 hours after biopsy. Conclusion. There was no statistically significant difference between the degree of sedation and the analgesic effect of the two regimens in the two groups.  DOI: 10.52547/ijkd.6982